PERANCANGAN DESAIN MARCHANDISE SEBAGAI STRATEGI BRANDING PARIWISATA BERBASIS TRADISI LISAN DI DESA TOYOMARTO KECAMATAN SINGOSARI KABUPATEN MALANG - Rahmawati, Femi Eka; Sukmawan, Sony; Syarifudin, Ahmad; syarifuddinr@ub.ac.id, Fitrahayunitisna (Faculty of Cultural Studies, Universitas Brawijaya, 2021)
Abstract: The existence of Toyomarto tourist village is expanding with the increasing number of tourists visiting the area. Visitors come for various purposes, ranging from religious (spiritual) activities to non-spiritual activities. As a village that has declared itself a tourist village, Toyomarto needs to formulate its image/identity so that it can be known by the wider public and have a stronger bargaining position compared to other villages. Therefore, Toyomarto needs to brand itself to become better, more advanced, and more developed. For this reason, a community service program titled “Design Planning as a Strategy for Tourism Branding Based on Oral Traditions in Toyomarto Village, Singosari District, Malang Regency” was initiated as a strategic program to brand Toyomarto as a tourist village among the wider community. Generally, this community service program is carried out through the utilization of research on local narratives (folk tales, myths, traditional arts, traditional expressions) found in Toyomarto Village. The local narratives will be specifically selected based on criteria related to water sources. Through a synthesis of various local narrative sources, these will be visualized in the form of graphic logo designs and illustrations, which can be applied as promotional media and unique merchandise based on the stories of Toyomarto Village.